2014
DOI: 10.1177/1534735414534462
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sasa quelpaertensis Nakai Leaf Extract and Cisplatin Suppresses the Cancer Stemness and Invasion of Human Lung Cancer Cells

Abstract: Lung cancer is the leading cause of cancer death worldwide, and most chemotherapeutic drugs have limited success in treating this disease. Furthermore, some drugs show undesirable side effects due to the enrichment of cancer stem cells (CSCs) that are present, leading to resistance to conventional chemotherapy and tumor relapse. CSCs possess self-renewal characteristics, aggressive tumor initiating activity, and ability to facilitate tumor metastasis. Therefore, development of nontoxic agents that can potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Sasa senanensis leaf extracts, which contain a higher level of phenolics have exhibited immunostimulation-mediated antitumor activity [ 47 ], while the antiproliferative and apoptotic effects of Sasa quelpaertensis Nakai have been reported in six human cancer cell lines, including A549, MCF-7, HeG-2, Hela, HCT116, and A375 [ 48 ]. Recently, it has also been reported that SQE alone, or in combination with cisplatin exerts anti-CSC and antimetastatic effects in H1299 and A549 human lung cancer cells by inhibiting the phosphorylation of phosphoinositide-3-kinase (PI3K) and by activating mammalian target of rapamycin (mTOR) [ 30 ]. To the best our knowledge, the present study is the first to demonstrate that SQE mediates an anti-colon cancer stemness effect by suppressing self-renewal, increasing cell differentiation, and inhibiting cell tumorigenicity of the colon CSCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sasa senanensis leaf extracts, which contain a higher level of phenolics have exhibited immunostimulation-mediated antitumor activity [ 47 ], while the antiproliferative and apoptotic effects of Sasa quelpaertensis Nakai have been reported in six human cancer cell lines, including A549, MCF-7, HeG-2, Hela, HCT116, and A375 [ 48 ]. Recently, it has also been reported that SQE alone, or in combination with cisplatin exerts anti-CSC and antimetastatic effects in H1299 and A549 human lung cancer cells by inhibiting the phosphorylation of phosphoinositide-3-kinase (PI3K) and by activating mammalian target of rapamycin (mTOR) [ 30 ]. To the best our knowledge, the present study is the first to demonstrate that SQE mediates an anti-colon cancer stemness effect by suppressing self-renewal, increasing cell differentiation, and inhibiting cell tumorigenicity of the colon CSCs.…”
Section: Resultsmentioning
confidence: 99%
“…Sasa quelpaertensis Nakai is native to Korea and is only grown on Mt. Halla (Jeju Island, Korea) [ 30 ]. Sasa quelpaertensis leaves contain a mixture of polysaccharides and polyphenols, including p -coumaric acid and tricin, which may mediate the anticancer effects observed for Sasa quelpaertensis extracts (SQE) [ 25 , 31 ] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SQE was a kind gift from Yong Chool Boo (Kyungpook National University, Daegu, South Korea). It was prepared and dissolved in distilled water (DW) as described elsewhere [5,20,21]. The yield of SQE from dried S. quelpaertensis leaves (1 kg) was approximately 10 %.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, other studies revealed that S. quelpaertensis Nakai extracts showed antiproliferation and apoptosis induction properties in human leukemia HL-60 cells (17), as well as in human and lung cancer A549 and H1299 cells. Despite previous reports demonstrated that potential clinical application of dwarf bamboo S. quelpaertensis Nakai extracts for prevention or treatment of neoplastic disease (19,23,24), the underlying mechanism has not been clarified.…”
Section: Discussionmentioning
confidence: 92%